Divalent Cations in Spray Water Influence 2, 4-D Efficacy on Dandelion (Taraxacum officinale) and Broadleaf Plantain (Plantago major). (June 2016) - Patton, Aaron J.; Weisenberger, Daniel V.; Johnson, William G.
Abstract : 2, 4-dichlorophenoxyacetic acid (2, 4-D) is a common ingredient in POST broadleaf herbicides labeled for use in turf, pastures, rangeland, and grain crops. The herbicide 2, 4-D is a weak acid, and when dissociated can bind to cations present in hard-water spray solutions and/or fertilizer solutions. Experiments were conducted with 2, 4-D dimethylamine to evaluate the effect of cation solutions on herbicide efficacy on the perennial broadleaf weeds dandelion and broadleaf plantain. The objectives of this research were to (1) determine if 2, 4-D efficacy is influenced by the divalent cations, calcium (Ca), magnesium (Mg), manganese (Mn), and zinc (Zn) in spray solution; and (2) determine if adding the adjuvant ammonium sulfate (AMS) to the spray solution can overcome antagonism. Broadleaf plantain and dandelion control was reduced and plant size and mass increased when 2, 4-D was applied in a Ca solution in comparison to deionized water. However, 2, 4-D antagonism was overcome when AMS was added as an adjuvant to the spray solution. Magnesium caused 2, 4-D antagonism on both weed species in one run of the experiment similar to Ca solution and AMS was successful at overcoming antagonism when added to the tank mixture. Some 2, 4-D antagonism from Mn was noticed even when AMS was in the tank mix, but Zn fertilizer solutions did not antagonize 2, 4-D activity on either weed species. Although divalent cations can antagonize 2, 4-D dimethylamine and reduce perennial broadleaf weed control, adding AMS can overcome this antagonism when Ca and Mg are the primary cations in spray solution. Applicators should avoid using Mn fertilizers when applying 2, 4-D dimethylamine because AMS did not successfully overcome antagonism.